Generation, transport, and efficient extraction of a large cross-section electron beam into an air in an accelerator with a mesh plasma cathode; Laser and Particle Beams; Vol. 36, iss. 1 - Vorobjev M. S. Mikhail Sergeevich; Koval T. V. Tamara Vasilievna; Koval N. N. Nikolay Nikolaevich; Nguyen Bao Khyng (2018, 2018)
Title screen